Peran Tasawuf dalam Mengatasi Krisis Masyarakat Modern - Malika Nofriza Sagita (Gunung Djati Conference Series, 2023)
The rapid development of industry, science and technology industrialization has influenced life, resulting in a shift in patterns and lifestyles, where moral and ethical values began to be abandoned because they were considered incompatible with modern values. This research aims to discuss the role of Sufism in overcoming the crisis of modern society. This research uses qualitative research methods by applying descriptive-analytical methods. The results of this study show that the teachings of Sufism in life will create a harmonious environment. In essence, Sufism aims to guide humans in order to achieve true closeness to God. Sufism is important for the life of modern society because Sufism can act as a human controller of the human dimension so as not to be eroded by the current of modernization and direct humans to values that are beyond sublime so that it will lead humans to moral perfection.